Strategi Mengajar Kimia (Lintas Minat) Melalui Modifikasi Leaderless Group Discussion (LGD) - Esdi Pangganti (FKIP Universitas Palangka Raya, 2018)
Chemistry subjects are often considered difficult subjects in the natural sciences majors, even more so if they are given in the social sciences majors as cross-interest subjects. The average student scored below the minimum completeness criteria, which is 75. In addition students look less active and do not have good motivation. This is possible because students feel that chemistry is a cross-interest subject, which has no significant influence on the direction of the social sciences . This phenomenon can be observed when the PBM process takes place some students seem less interested and cannot focus themselves on learning the material being studied, as well as during the discussion process students tend not to be involved and have a low response. One of the success of the teaching and learning process is determined by the teaching model or method, namely how the teacher delivers the material to be taught. Leaderless Group Discussion is a group discussion without the appointment of a leader, which allows each group member to manifest his potential, modified like an Exhibition Stand Guard. In this simulation one can observe the ability of a person to direct and lead a group, the ability to explain ideas so that they can be accepted by others, the ability to determine, etc. The results of the application of learning with the Modified Leaderless Group Discussion approach can increase the participation of class XI students majoring in Social Sciences in learning Cross-Interest Chemistry reached 88.69% with completeness reaching 89.66% (26 people).